Money literacy, shopping and purchasing patterns among primary school students in Malaysia - Wahab, Rozita; Sabri, Mohamad Fazli; Ramli, Nurhayatul Nira (American Research Institute for Policy Development, 2016)
The purpose of this study was to identify the understanding of money literacy, shopping and purchasing patterns among primary school students in Malaysia. This study was conducted among 800 primary school students who were randomly selected using multistage sampling from five different states in Malaysia, including East Malaysia. Money literacy was measured using 11 questions related to subject while shopping and purchasing patterns were measured using 12 questions related to subject. Results showed that primary school students in Malaysia have moderate understanding regarding money. Most of the students understand only on the subjects that involved in their daily routines but they are lacking in other money matters which were not directly related or experienced by them. Results also showed that the patterns of spending and purchasing of primary school students in Malaysia still need changes for the better. Parental involvement or influences in the purchasing patterns of the students were low, plus the results also showed that there were less discussions about expenses between the two sides; parents and students. Surprisingly, findings also showed that there were already indebted practices among the students who are still in primary school and it is at high percentages.